2011
DOI: 10.1108/aaouj-06-01-2011-b006
|View full text |Cite
|
Sign up to set email alerts
|

Developing Quality Learning Materials for Effective Teaching and Learning in an ODL environment: Making the jump from print modules to online modules

Abstract: This paper highlights the need to develop quality learning materials for effective teaching and learning in an online

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
(2 reference statements)
1
6
0
2
Order By: Relevance
“…Column B and eBook Sig shows the range of 5.573 points which means that if students use eBooks, their learning outcomes will be higher by 5.573 points compared to those using printed books. It can be concluded that the use of eBooks in rural schools is able to further improve students' learning outcomes compared to the use of printed book s. Some of the studies that support these findings are those of Lai (2016), Liaw & Huang (2014), Chen (2013), Bradshaw (2005), Goodwin (2014), Woo (2011), Massis (2010, Bronshteyn (2007), deNoyelles & Seilhamer (2013), Tucker (2012), Letchumanan & Muniandy (2016), Rojeski (2012), and Parkes (2007). The results that contradict these findings explain that the printed book is still relevant (Jeong, 2012;Katsarska, 2005;Lewellen, Bischof, & Plum, 2016;Nwagwu & Okafor, 2014;Darsono, Wi narno, & Slamet, 2018).…”
Section: Result Discussion and Suggestionsmentioning
confidence: 95%
“…Column B and eBook Sig shows the range of 5.573 points which means that if students use eBooks, their learning outcomes will be higher by 5.573 points compared to those using printed books. It can be concluded that the use of eBooks in rural schools is able to further improve students' learning outcomes compared to the use of printed book s. Some of the studies that support these findings are those of Lai (2016), Liaw & Huang (2014), Chen (2013), Bradshaw (2005), Goodwin (2014), Woo (2011), Massis (2010, Bronshteyn (2007), deNoyelles & Seilhamer (2013), Tucker (2012), Letchumanan & Muniandy (2016), Rojeski (2012), and Parkes (2007). The results that contradict these findings explain that the printed book is still relevant (Jeong, 2012;Katsarska, 2005;Lewellen, Bischof, & Plum, 2016;Nwagwu & Okafor, 2014;Darsono, Wi narno, & Slamet, 2018).…”
Section: Result Discussion and Suggestionsmentioning
confidence: 95%
“…Apart from that, the quality of learning materials is also important in ODL. According to Woo (2011), modules in OUM comprise a number of good HTML characteristics. Those characteristics are 1) html module should allow nonlinear learning; 2) encourage exploratory learning; 3) respect different learning styles; 4) state learning outcomes; 5) communicate high expectation; and 6) promote interaction and interactivity.…”
Section: Literature Studiesmentioning
confidence: 99%
“…Those characteristics are 1) html module should allow nonlinear learning; 2) encourage exploratory learning; 3) respect different learning styles; 4) state learning outcomes; 5) communicate high expectation; and 6) promote interaction and interactivity. She also added that although she found some researchers who are doubtful about interaction in ODL, while others believe that ODL and Overall Program Structure from ODL Students' Perspective programs can be more interactive than traditional one with proper interaction design (Woo, 2011).…”
Section: Literature Studiesmentioning
confidence: 99%
“…The effectiveness of the use of experiential learning-based teaching material in Mathematics in improving the student cognitive ability is supported by the relevant researches. The researches carried out by Amir, et al [19], and Woo [20] prove that the learning which uses the teaching material can improve the student learning result. The researches which also conducted by Tanaka, et al [21], Matias and Gonzalez [22], Arthur and Raine [23], and Judge, et al [24] prove that experiential learning can give the good opportunity for the students and the student will be interested in the learning process since they are given the concrete examples in the daily life.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%